Incongruent patterns of genetic connectivity among four ophiuroid species with differing coral host specificity on North Atlantic seamounts - Walter Cho; Timothy M. Shank (Marine Ecology, 2010)
Seamounts are considered to play a defining role in the evolution and diversity of marine fauna, acting as ‘stepping‐stones’ for dispersal, regional centers of genetic isolation and speciation, and refugia for deep‐sea populations. This study focused on the patterns of dispersal and genetic connectivity of four seamount ophiuroid species ( Asteroschema clavigera , Ophiocreas oedipus , Ophioplinthaca abyssalis , and Ophioplinthaca chelys ) displaying differing levels of associative (epifaunal) specificity to cold‐water coral hosts inhabiting the New England and Corner Rise Seamount chains, and Muir Seamount in the Northwestern Atlantic. Analyses of mt16S and mtCOI revealed evidence for recent population expansion and high gene flow for all four species. However, species‐specific genetic differentiation was significant based on seamount region and depth. Significant differences were found among regional seamount groups for A. clavigera , within seamount regions and seamounts for O. chelys , among 250‐m depth intervals for A. clavigera , among 100‐m depth intervals for O. oedipus , and there were indications of isolation by distance for A. clavigera and O. oedipus . In addition, A. clavigera and O. oedipus , broadcast spawners with high fidelity to specific coral hosts, displayed predominantly westward historical migration, whereas the ophioplinthacids, with lower host‐specificity, displayed predominantly eastward migration. No congruent patterns of historical migration were evident among species and seamounts, yet these patterns can be correlated with species‐specific host specificity, specific depth strata, and dispersal strategies. Conservation efforts to protect seamount ecosystems should promote multi‐species approaches to genetic connectivity, and consider the impact of the ‘dependence’ of biodiversity on host fauna in these vulnerable marine ecosystems.